Modified Sinus Lifting using the pillow technique. Clinical case report (Research, Society and Development, 2021)
Due to the need for rehabilitation with dental implants, maxillary sinus lifting surgery is described as a safe technique, in this case report we demonstrate a modified maxillary sinus lifting technique, the pillow technique, in which a pillow is made with a absorbable membrane filled with bone graft. At the time of surgery, the side window technique with displacement of the Schneider membrane and insertion of the pillow is used. As a clinical result, a satisfactory amount of bone gain was observed in the 11-month postoperative period. With this technique, it is possible to obtain a shorter surgical time due to the need only for the preparation of the receiving bed, since the pillow is made prior to the surgical act, in addition to a new maneuver for the protection of the biomaterial in cases of perforations of the Schneider membrane decreasing the chance of postoperative complications.